A SINGLE CENTRE 20 YEARS’ EXPERIENCE AND OUTCOME OF BILATERAL ADRENALECTOMY - WA, Siti Sanaa; H, Zanariah; B, Anita (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Bilateral adrenalectomy is an extremely rare operation performed due to its limited indications. Only 1-6% of patients undergoing adrenal surgery needed a bilateral procedure. METHODOLOGY This is a retrospective medical records review of all patients who underwent bilateral adrenalectomy from 2000 to 2020. RESULTS Between 2000-2020, a total of 22 patients (5 male, 17 female) underwent bilateral adrenalectomy, simultaneous procedure was performed for sixteen patients while the remaining had sequential adrenalectomy at an interval of 7 months-12 years from the first surgery. Mean age was 38.2 years (range 21- 72), mean duration of follow-up was 66 months (range 1-252 months). Two patients died at 3 and 10 months post-surgery due to sepsis. The indications for surgery were bilateral pheochromocytoma in 59% (n=13) of which six patients were MEN2A-associated, and one with SDHD-related disease. Eight patients (36%) had Cushing’s syndrome (CS) of which half were ectopic CS (ECS) (3 malignant mediastinal NET, one unlocalised ECS), one patient with refractory Cushing’s Disease and three with CS due to bilateral adrenal pathology which comprised of two patients with primary pigmented nodular adrenocortical disease (PPNAD) as part of Carney Complex, and one patient with ACTH-independent macronodular adrenocortical hyperplasia (AIMAH). There was a single case of primary aldosteronism due to bilateral adrenal hyperplasia with refractory hypertension. This patient underwent sequential adrenalectomy. Five patients (22.7%) underwent adrenal sparing surgery but adrenocortical function was preserved in only two patients. 91% were maintained on physiological replacement doses of hydrocortisone 15–20 mg in two to three divided doses and seven (32%) patients required concomitant fludrocortisone replacement at a dose of 0.05–0.1 mg daily. CONCLUSION Bilateral adrenalectomy is advocated in a small population of patients, and adrenal sparing surgery may be considered in a subgroup of patients with familial pheochromocytoma. Extra caution should be anticipated and exercised in patients with pre-existing severe uncontrolled hypercortisolaemic state.